Rice bran attenuated obesity via alleviating dyslipidemia, browning of white adipocytes and modulating gut microbiota in high-fat diet-induced obese mice. Issue 3 (4th March 2020) - Zou, Yucheng; Ju, Xingrong; Chen, Wenye; Yuan, Juan; Wang, Zhigao; Aluko, Rotimi E.; He, Rong
Abstract : Rice bran supplementation played a significant role in reducing dyslipidemia and inflammation, enhancing browning of white adipocytes and modulating gut microbiota for the prevention and control of obesity. Abstract : Obesity has become an international public health problem. In this study, an obese mice diet was supplemented with raw rice bran (RRB) or infrared radiation-stabilized rice bran (IRRB) to investigate the attenuation of obesity induced by a high-fat diet. Mice were fed a normal diet or a high-fat diet with and without rice bran supplementation (300 mg per kg body weight per day) by oral gavage for 39 days to investigate the obesity preventive effect. The results indicate that different rice bran supplements reduced body weight, relative adipose tissue weight, inflammation, and serum parameters, and relieve liver steatosis to varying degrees. The data of real-time qPCR and western blots (WB) showed that rice bran activated brown adipose tissue (BAT) and increased white adipose tissue (WAT) browning. Rice bran also reduced the ratio of Firmicutes / Bacteroidetes and enhanced the relative abundance of Akkermansia . In summary, our findings suggest that rice bran intervention played a significant role in reducing dyslipidemia, alleviating inflammation, enhancing thermogenesis and modulating gut microbiota for the prevention and control of obesity.